Fatigue‐related group III/IV muscle afferent feedback facilitates intracortical inhibition during locomotor exercise. (3rd September 2018) - Sidhu, Simranjit K.; Weavil, Joshua C.; Thurston, Taylor S.; Rosenberger, Dorothea; Jessop, Jacob E.; Wang, Eivind; Richardson, Russell S.; McNeil, Chris J.; Amann, Markus
Abstract : Key Points: This study investigated the influence of group III/IV muscle afferents on corticospinal excitability during cycling exercise and focused on GABAB neuron‐mediated inhibition as a potential underlying mechanism. The study provides novel evidence to demonstrate that group III/IV muscle afferent feedback facilitates inhibitory intracortical neurons during whole body exercise. Firing of these interneurons probably contributes to the development of central fatigue during physical activity. Abstract: We investigated the influence of group III/IV muscle afferents in determining corticospinal excitability during cycling exercise and focused on GABAB neuron‐mediated inhibition as a potential underlying mechanism. Both under control conditions (CTRL) and with lumbar intrathecal fentanyl (FENT) impairing feedback from group III/IV leg muscle afferents, subjects ( n  = 11) cycled at a comparable vastus‐lateralis EMG signal (∼0.26 mV) before (PRE; 100 W) and immediately after (POST; 90 ± 2 W) fatiguing constant‐load cycling exercise (80% Wpeak; 221 ± 10 W; ∼8 min). During, PRE and POST cycling, single and paired‐pulse (100 ms interstimulus interval) transcranial magnetic stimulations (TMS) were applied to elicit unconditioned and conditioned motor‐evoked potentials (MEPs), respectively. To distinguish between cortical and spinal contributions to the MEPs, cervicomedullary stimulations (CMS) were used to elicit unconditioned (CMS only) and conditioned (TMS+CMS, 100 ms interval) cervicomedullary motor‐evoked potentials (CMEPs). While unconditioned MEPs were unchanged from PRE to POST in CTRL, unconditioned CMEPs increased significantly, resulting in a decrease in unconditioned MEP/CMEP ( P  < 0.05). This paralleled a reduction in conditioned MEP ( P  < 0.05) and no change in conditioned CMEP. During FENT, unconditioned and conditioned MEPs and CMEPs were similar and comparable during PRE and POST ( P  > 0.2). These findings reveal that feedback from group III/IV muscle afferents innervating locomotor muscle decreases the excitability of the motor cortex during fatiguing cycling exercise. This impairment is, at least in part, determined by the facilitating effect of these sensory neurons on inhibitory GABAB intracortical interneurons. Key Points: This study investigated the influence of group III/IV muscle afferents on corticospinal excitability during cycling exercise and focused on GABAB neuron‐mediated inhibition as a potential underlying mechanism. The study provides novel evidence to demonstrate that group III/IV muscle afferent feedback facilitates inhibitory intracortical neurons during whole body exercise. Firing of these interneurons probably contributes to the development of central fatigue during physical activity.